Antropologia Metodego z Olimpu - Mejzner, Miroslaw (Vox Patrum, 2025)
The article aims to present the key elements of the anthropology of Methodius of Olympus, which include: the creation of man in the image and likeness of God as a spiritual and bodily unity; the degradation of human nature through the sin of disobedience; redemption in Christ; the spiritual and moral development of the Christian, especially through the virtue of chastity; the passage through the gate of death; the resurrection and the fullness of life in the world of the redeemed. Particular attention will be given to the exegesis of the Bishop of Olympus and his dependence on early Christian theological traditions—specifically the Asia Minor and Alexandrian traditions—which he sought to combine creatively, though not without difficulties. The coherence of the author’s thought will also be emphasized, especially the consistency of his protological, soteriological, and eschatological assumptions, as well as those pertaining to spirituality and asceticism.